Efficacy of transrectal ultrasonography (TRUS) in preoperative staging of rectal cancer - Pavlovic Markovic, Aleksandra; Barisic, Goran; Nincevic, Jelena; Milovanović, Tamara; Garalejic, Elijana; Stojkovic Lalosevic, Milica; Krivokapic, Zoran (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The outcome of rectal cancer is dependant on the stage of the tumour. There are several classification systems used to describe the extent of the disease. The aim of this study was to compare the efficacy of transrectal ultrasonography (TRUS) in preoperative local staging of rectal cancer using endosonographic probes with different views (180° vs 360°), as well as an influence of experience of an endoscopist on the TRUS performance. Methods. TRUS was performed in 127 patients with rectal carcinoma by two endoscopists. Seventy-one patients were examined with a 180° endosonographic probe (group A) and 56 patients with a 360° rotating probe (group B). All findings were compared with a histopathology report. Results. TRUS had a diagnostic overall accuracy of 91.3% for the tumor (T) category (k = 0.866, SE (k) = 0.038, p < 0.0001) and 71.7% for the node (N) category (κ = 0.374, SE (k) = 0.082, p < 0.0001). In the group A, TRUS had a diagnostic overall accuracy of 88.7% for the T category (κ = 0.805, SE (k) = 0.063, p < 0.0001), and 70.4% for the N category (κ = 0.376, SE (k) = 0.101, P < 0.0001). In the group B, TRUS had a diagnostic overall accuracy of 94.6% for the T category (κ = 0.920, SE (k) = 0.044, p < 0.0001), and 73.2% for the N category (κ = 0.379, SE (k) = 0.131, p = 0.004). Experience of the endoscopist had no significant influence on results of preoperative staging of rectal cancer by using TRUS. Conclusion. The accuracy rate of TRUS in the preoperative local staging of rectal cancer is high. Our results imply no significant difference in the overall accuracy rates when using endosonographic probes with different views (180° vs 360°). Also, there was no significant influence of endoscopist experience on results obtained.
Keywords: rectal neoplasms; carcinoma; neoplasm staging; preoperative period; ultrasonography; diagnosis, differential